INDONESIA'S DIGITAL TALENT POLICY READINESS - Binti azizatun Nafi'ah (Jurnal Penelitian Administrasi Publik, 2021)
Digital transformation creates new digital skills. McKinsey & company estimates that by 2030 at least 23 million jobs will be lost and replaced by automation. But at the same time, 27-46 million new jobs can be created with this technology. This causes a skill gap due to the demand for new digital skills on the labor market. This research focuses on analyzing the readiness of the Indonesian government in overcoming this digital skill gap. This research is a qualitative research with primary and secondary data collection. As a result, the Indonesian government is not ready to solve the digital skill gap. This can be seen from the incomplete development of IT infrastructure in the villages and the existing training has not been maximized and has not been accompanied by an internship.